Performance Analysis of MIA Algorithm for LDPC Codes in near Space Rain Attenuation Channel - Su, Yi Dong; Wu, Hao; Chen, Shu Xin (Applied Mechanics and Materials, 2011)
According to the influence of grand reflector to the channel, near space Ka-band rain attenuation channel model of area coverage is improved. According to RRWBF algorithm and UMP BP-Based algorithm of LDPC codes, a mixed iterative decoding algorithm is proposed. The algorithm takes advantage of low complexity of hard-decision algorithm and high performance of soft-decision algorithm, so in near space rain attenuation channel, the decoding complexity significantly reduced when bit error rate performance does not decline. Simulation results show that in near space rain attenuation channel, MIA algorithm can reduce decoding complexity by about 30%, compare with the UMP BP-Based algorithm.